Grundtvig i økumenisk perspektiv - Lodberg, Peter (Grundtvig-studier, 1998)
Grundtvig in an Ecumenical Perspective By Peter LodbergN.F.S. Grundtvig’s theology has often been perceived as a uniquely Danish phenomenon. This has resulted in a failure to appreciate the ecumenical themes in his theology and has precluded a positive consideration of what impulses his comprehensive work may have added to the ecumenical debate about such issues as practical theology, ecclesiology, and the relationship between Scripture and tradition.The article points out that in order to understand Grundtvig’s church view it is absolutely essential to begin with the Danish version of a classical discussion in ecumenical theology: the relationship between justification and church, christology and ecclesiology, as it manifested itself in the discussion between Grundtvig and H.N. Clausen about the nature of Catholicism and Protestantism.In Kirkens Gienmæle (The Rejoinder of the Church), Grundtvig rejects the attempt by modem Protestantism to establish a fundamental difference between the two versions of the understanding of Christianity in the Western Church as far as the question of the relationship between justification and church is concerned. According to Grundtvig, such an attempt is bound to end in heresy, since it fails to appreciate the actual historical church as the bearer of God’s salvation in the world. Instead Grundtvig emphasizes an ecumenical ecclesiology, starting from a common confession of the Apostles’ Creed, Baptism and Communion, which are the unifying elements of all Christians, regardless of differences in theological dogma. Hence follows that there is no fundamental difference between Catholicism and Protestantism, but a shared basic view as far as the content and celebration of faith is concerned.Thus, what Grundtvig achieves is a theological freedom to remain critical of the transformations undergone by the historical church in its many confessional and national versions through the ages. But at the same time this means that there is a decisive systematic-theological point in emphasizing that Grundtvig always speaks about the Christian Church before he speaks about the confessional or national church. It should be stressed at the same time that the all-Christian church is not invisible or an unattainable ideal, but a historical fact when the congreation is gathered for divine service. Here the Gospel and the Holy Communion is administered to people, so the faith must live in their hearts.Grace is thus inseparable from and dependent on the sacramental presence as it is experienced in the church which is the congregation celebrating divine service. Thus the way has been opened for a positive consideration of Grundtvig’s contributions to ecumenical theology.